The Economics of Co-ethnic Employment; Incentives, Welfare Effects and Policy Options - Frank A.G. den Butter; Enno Masurel; Robert Mosch (Tinbergen Institute, 2004)
Co-ethnic employment refers to the stylised fact of many labour markets that there is an over-representation of workers of the same ethnic group within firms. This paper presents empirical proof of the phenomenon and analyses the incentives for employees to work in co-ethnic firms. It argues that strong social networks and related high intra-group trust constitute the major reasons for co-ethnic employment by lowering information and co-ordination costs. In the short run, co-ethnic employment leads to more jobs for employees, easy access to labour for ethnic minority firms, strengthening of the group values and norms, and less unemployment and social security problems for society. In the long run, co-ethnic employment might form an obstacle to the social and economic emancipation of ethnic minority groups. It generates disincentives for individual group members to acquire general skills, hinders the development of ethnic minority firms, fosters the danger! of the ethnic trap and stimulates the emergence of an enclave economy.
Keywords: J61; Z13; 330; co-ethnic employment; social capital; trust; networks; Ethnische Gruppe; Erwerbstätigkeit; Social Capital; Netzwerk; Niederlande; Migranten